2-Methylbenzimidazolium thiocyanate-2-methylbenzimidazole (1/1) - Shaker, S.A.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2010)
In the crystal structure of the title compound, C(8)H(9)N(2)(+)center dot-SCN(-)center dot C(8)H(8)N(2), the three components are linked by intermolecular N-H center dot center dot center dot N and N-H center dot center dot center dot S hydrogen bonds into infinite chains along the c axis.